The Impact of Gross Regional Domestic Product towards the Relationship of the Permanent Investment and Fix Assets with Domestic Inventive Income - Maryani Maryani (Politeknik Negeri Lampung, 2014)
The purposes of this study are to investigate the effect of Gross Regional Domestic Products (GRDP) on the relationship between permanent investment and fixed assets with domestic inventive incomes. To achieve the aim of the study, a research conducted in Bandar Lampung city. Based on generated data, hypotheses tested using LIRSEL. According to statistical analysis, found that: 1) permanent investment has a positive correlation on GRDP, 2) Fixed assets are not significantly influence GRDP, 3) Permanent Investment has a positive influence on domestic inventive income, and 4) fixed assets has not a positive impact on domestic inventive income. This study seems that only permanent investment that tends to have indirect influence from domestic inventive income and GRDP.Key words: Gross Regional Domestic Product, Domestic Inventive Incomes, Permanent Investments, Fixed Assets